Regi med feministiska förtecken, I lusthuset på Unga Klara - Svens , Christina (Tidskrift för genusvetenskap, 1997)
How can a director's involvement with feminism influence h e r practice? In this a r t i d e this question is adressed through looking at the director Suzanne Osten and her production of the play I Lusthuset / T h e Summer-house/ f r om 1988/89. Osten tries different ways of i n t r o d u c i n g a feminist discussion i n t o all aspects the p r o d u c t i o n of the play. Through f o rm as well as theme the feminist approach is focusing on the m e t h o d by which Osten chooses to articulate her message as well as how this message relätes to s u r r o u n d i n g social norms.